Costo de contaminación del sector pecuario en Colombia (2018)
The environmental commitment that each country has with the rest of the world implies that, based on the different disciplines of knowledge, tools are developed to cope with the phenomenon of climate change. In this study, we intend to use the mechanisms that authors like Fèare, Chung and Chambers (1996) have designed and implemented in order to make visible the phenomenon of pollution within the economic discipline. During the development of this text, and with the help of directional distance functions, the opportunity cost (shadow price) of greenhouse emissions, specifically emissions of CH4 (methane) for the livestock sector (bovine cattle) in Colombia is estimated in quantifiable units of GHG. The results show that there is indeed a cost of contamination associated with the livestock sector, which varies for each department given its level of efficiency but which tends to remain stable over the years.